Market Size and Export-Led Growth Hypotheses: New Evidence from Malaysia - Hassan, Sallahuddin; Murtala, Musa (International Journal of Economics and Financial Issues, 2016)
Exploring the causal relationship among exports, FDI and economic growth is of enormous importance for the policy implications the causal process among the variables assume. The relevance of investigating the causal relationship between inward FDI and exports borders on the implications of the choice between outward oriented policy and inward looking policy. Utilizing data on Malaysia spanning 1970 – 2012, this study explores the relationships as well as causal interactions among economic growth, exports and FDI employing Vector Autoregression (VAR) model and Toda and Yamamoto (1995) augmented causality test. Results from impulse response function (IRF) analysis shows that both real GDP and real FDI have increasing trend of percentage shocks in them causing fluctuations in the real exports over the period of 5 years. However, real exports was found to have dominance of own shock over the period of analysis. Similarly IRF of real FDI shows that flections in the variable are dominated by variations in its own values. However, both real exports and real FDI were found to have significant effect in determining fluctuation in real FDI with real GDP having stronger effect. Finally, we observe very significant effect on fluctuations in real GDP of real FDI and exports. Over the course of five years, it was observed that real FDI and exports dominate fluctuations in the real GDP more than its own shock. Results from the study indicate presence of bi-directional causality between exports and inward FDI. On the causal link between exports and GDP, the study finds evidence of uni-directional causality running from GDP to exports, affirming Growth-Led Exports (GLE) hypothesis. The study also provides evidence that market size hypothesis holds for Malaysia, as evident by one-way causality from GDP to FDI. Keywords: Growth-led exports hypothesis, Market size hypothesis, y, exports, FDI, real GDP, Malaysia JEL Classifications: F4, O47